Cognitive improvement of acetylcholinesterase inhibitors in schizophrenia. (November 2018) - Santos, Borja; González-Fraile, Eduardo; Zabala, Arantzazu; Guillén, Virginia; Rueda, José R; Ballesteros, Javier
Background: Schizophrenia is a severe, persistent mental disorder, and a leading cause of disability worldwide. Cognitive impairments presented in schizophrenia lead to a worse prognostic, thus treatments targeted to enhance cognition in schizophrenia may be clinically relevant. Aims: The purpose of this study was to assess the efficacy of acetylcholinesterase inhibitors as add-on medication to antipsychotics on cognition in patients with schizophrenia. Methods: Search strategies were developed for Medline, Embase and Cochrane Central Register of Controlled Trials, and are current to March 2018. We included randomised controlled trials that compared antipsychotics plus acetylcholinesterase inhibitors versus antipsychotics plus placebo on prespecified cognitive domains (speed of processing, attention and working memory). Two review authors independently evaluated study eligibility, extracted data and assessed the risk of bias of included studies. We used random-effects model for meta-analyses and assessed the quality of evidence using Grading of Recommendations Assessment, Development and Evaluation (GRADE). Results: We included nine randomised controlled trials. Six randomised controlled trials ( n =219) presented evidence that acetylcholinesterase inhibitors improve speed of processing (standardised mean difference −0.52, 95% confidence interval (−0.79 to −0.25); p value=0.0002). However, eight randomised controlled trials ( n =252) did find placebo was better than acetylcholinesterase inhibitors in the attention domain (−0.43, (−0.72 to −0.13); p value=0.005) and eight randomised controlled trials ( n =273) did not find differences in the working memory (−0.14, (−0.51 to 0.24), p value=0.47). Conclusions: The current evidence is too weak to base recommendations on the use of acetylcholinesterase inhibitors as adjunctive treatments to antipsychotics to improve basic cognitive functions. We have limited confidence in the effect estimates.